Changes in Defensive Variables Determining Success in the NBA over the Last 10 Years - Buyukcelebi, Hakan; Sahin, Fatma Nese; Acak, Mahmut; Uysal, Huseyin Sahin; Sari, Cengizhan; Erkan, Dilara; Yatak, Semra (Mdpi, 2024)
This study aimed to determine changes in defensive strategies over the past decade in the National Basketball Association (NBA) and identify the most crucial factors for winning games. The study analyzed all games where the 30 NBA teams played over 11 seasons (13,530 games) and created outcome statistics based on win-loss records. Five defensive variables (OREB [offensive rebound], DREB [defensive rebound], TREB [total rebound], ST [steal] and BLK [block]) were compared, revealing that OREB (p < 0.03), DREB (p < 0.001), TREB (p < 0.001), ST (p < 0.001) and BLK (p < 0.001) occur significantly in winning teams. Also, it has been observed that the changes over the years in the variables OREB (p < 0.01), DREB (p < 0.01), TREB (p < 0.01) and ST (p < 0.01) are statistically significant. However, there was no significant difference in the BLK variable over the years (p = 0.24). The impact of defensive variables on winning and their factor loadings are as follows: DREB (lambda = 0.50), ST (lambda = 0.15), TREB (lambda = 0.10), BLK (lambda = 0.08) and OREB (lambda = 0.06). Coaches can use these findings on defensive variables to strategize and counter opponents during games.
Keywords: basketball; analysis; NBA; defense; team performance